Government Policy Evaluation on Parking Management for Commercial Buildings: Implications for Educational Management and Public Service Effectiveness - Mhd Alfayet; Rahmadani Yusran (Journal of Educational Management Research, 2026)
This study aims to evaluate government policies in the arrangement and security of parking facilities for commercial buildings by integrating an educational management perspective, particularly in relation to policy planning, coordination, supervision, and stakeholder participation as learning processes within public sector governance. The evaluation framework is based on the theory of Egon G. Guba and Yvonna S. Lincoln, which includes five indicators: effectiveness, efficiency, responsiveness, suitability, and policy impact. This research employed a qualitative descriptive method using in-depth interviews, observations, and document analysis involving eleven informants from relevant government agencies, law enforcement units, business actors, parking attendants, and community members. The findings indicate that the implementation of parking policies has not been effective or efficient due to weak inter-agency coordination, limited supervision mechanisms, and inadequate parking infrastructure. From an educational management perspective, these weaknesses reflect insufficient institutional learning, lack of systematic capacity development, and limited dissemination of policy understanding among implementers and stakeholders. Nevertheless, responsiveness is relatively strong, as authorities promptly address public complaints through established communication channels. Although the policy aligns with urban planning objectives, it has not been adaptive to the rapid growth of vehicles and economic activities. The policy impact on traffic order and public comfort remains partial, with persistent issues of illegal parking and congestion. The study implies that strengthening educational management principles such as continuous institutional learning, competency based training, digital supervision systems, and community-based policy education is essential to improve the effectiveness and sustainability of parking policy implementation